Self-reporting hydrogels rapidly differentiate among enterohemorrhagic Escherichia coli (EHEC) and non-virulent Escherichia coli (K12). (August 2016) - Sadat Ebrahimi, Mir-Morteza; Dohm, Nina; Müller, Mareike; Jansen, Bernd; Schönherr, Holger
Graphical abstract: Highlights: Novel autonomously reporting hydrogels for the signaling of α‐ and β‐galactosidase. Enterohemorrhagic E. coli O157:H7 (EHEC) can be differentiated from E. coli K12. Orthogonal response of enzymes β‐galactosidase and β‐glucuronidase shown. Direct determination of bacterial enzyme concentration in supernatants is feasible. Abstract: We report on the development of an autonomously reporting indicator hydrogel for the rapid and selective detection of enzymes secreted by the food-borne biosafety level 3 pathogen enterohemorrhagic Escherichia coli ( E. coli ) O157:H7 (EHEC) and the differentiation of this pathogen from the non-virulent E. coli strain K12. To introduce the sensing functionality, chitosan hydrogel films were equipped with fluorogenic substrates for the detection of α-galactosidase (α-Gal) and β-galactosidase (β-Gal), which are secreted by E. coli O157:H7, and β-glucuronidase (β-GUS), which is produced by the non-virulent E. coli K12 strain, but not by E. coli O157:H7, respectively. In the presence of the bacteria and concomitantly the corresponding enzymes, the fluorophore 4-methylumbelliferone is selectively liberated and signals the presence of bacterial enzymes. To elucidate the response of the hydrogel sensors and to confirm the selectivity pattern allowing one to differentiate the pathogenic from the non-virulent E. coli strain, the enzymatic reactions were studied systematically in enzyme solutions as well as various bacterial supernatants. α-Gal was found to be produced by both E. coli K12 and E. coli O157:H7 in concentrations that are too low to be detectable in supernatants by the self-reporting hydrogels. By contrast the self-reporting hydrogels were shown to detect β-Gal secreted by E. coli O157:H7 within less than 4 h. A corresponding enzyme concentration of ∼7 × 10 −8 U/mL was determined from the analysis of the apparent reaction kinetics. Since the chitosan hydrogel can be applied as a coating on various substrates, the results of this proof of principle work indicate the feasibility of autonomously reporting indicator coatings for potential application in microbiological diagnostics and food safety.